Actuality and happiness of the soul: An Islamic epistemological perspective - Nani Widiawati (Institut Agama Islam Negeri Langsa, 2021)
Securing the focus of the study on psychological facts carried out by psychology to pass the scientific test still leaves a problem of definition. Such an identity crisis will be reconciled by using an Islamic epistemological perspective that incorporates conceptual-metaphysical studies as part of the scientific tradition by applying it to the analysis of the actualization of the function of the human soul. This paper aims to analyze the actualization of the potential of the human soul, the actuality or potentiality of human soul health, and the relevance of soul health to the happiness of the human soul. The theme of this paper uses qualitative research, literature study design, theoretical hermeneutic methods, content analysis techniques, and the author as a research instrument. It is known that the perfect actualization of the rational soul is the soul’s arrival at divine truth in theory and practice. The actualization of soul function in a person shows the level of his/her soul health. A happy soul is found in this healthy soul, namely a soul that has been freed from material tendencies and spiritual diseases. It also leads actions to the noble character and has longing and submission to God. These theoretical findings can be used to develop empirical-experimental research in psychology.